¿Cómo valorar los planes de pensiones del sistema individual en España? - García, Yaiza; Garcia, Juan (Estudios de Economía, 2016)
We analyse diverse multifactor pricing models in order to determine if they allow to explain the variability of the returns on the personal Pension Plans in Spain between 1995 and 2003, as well as to find their sources of risks. We test the following models: APT, the one suggested by Chen, Roll and Ross (1986) and a model constituted mainly with factors of the fixed-income market. The results obtained indicate that the fundamental factors in the pricing of the Personal Pension Plans are associated with the fixed-income market (maturity, default risk, relevance of short term operations).